Porous rod-like carbon nitride photocatalytic material as well as preparation method and application thereof
By constructing porous rod-shaped carbon nitride material, using hydrothermal reaction method of melamine and urea, centrifugal washing and high-temperature calcining steps of phosphoric acid solution, the problem of insufficient photocatalytic activity of existing graphite phase carbon nitride materials is solved, and high-efficiency photocatalytic degradation and excellent practical application potential are achieved.
Patent Information
- Application Number
- CN202510081814.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The specific surface area of existing graphite phase carbon nitride materials is low and the pore distribution is uneven, which limits its photocatalytic activity and electron-hole separation efficiency, affecting its practical application performance in pollutant degradation.
By constructing a porous rod-like carbon nitride material, using a hydrothermal reaction method of melamine and urea, combined with centrifugal washing of phosphoric acid solution and high-temperature calcination steps, a porous rod-like carbon nitride composite material with high specific surface area and uniform pore distribution was prepared.
It significantly improves the photocatalytic activity of the material, achieves efficient photocatalytic degradation, avoids secondary pollution of by-products, and shows excellent practical application potential.
Smart Images

Figure HDA0005248883990000011 
Figure HDA0005248883990000012 
Figure HDA0005248883990000013
Abstract
Description
Technical Field
[0001] The invention relates to a new structure carbon nitride material and a preparation method and application thereof, in particular to a porous rod-shaped carbon nitride material and a preparation method thereof and application thereof in removing iodinated contrast agents by visible light catalytic activation, belonging to the technical field of water treatment. Background Art
[0002] In recent years, photocatalytic water treatment technology has attracted widespread attention in the field of pollutant degradation due to its high efficiency, environmental friendliness and sustainability, which has subsequently promoted the research and application of photocatalytic materials. As a typical photocatalytic material, graphite carbon nitride has received widespread attention in recent years due to its excellent chemical stability, unique electronic structure and low preparation cost. However, ordinary graphite carbon nitride usually exhibits a blocky or disordered stacking structure with a low specific surface area and uneven pore distribution, which limits its photocatalytic activity and electron-hole separation efficiency, thereby affecting its actual application performance in pollutant degradation. To this end, optimizing and adjusting its structure has become a key research direction to improve the photocatalytic performance of graphite carbon nitride.
[0003] To overcome the above limitations, researchers have tried to improve the photocatalytic performance of graphite carbon nitride by structural modification. Among them, the modification methods usually include introducing porous structures, regulating the dimensions of materials (such as one-dimensional and two-dimensional materials), constructing heterojunctions, and doping specific elements. The porous structure can significantly improve the adsorption capacity of pollutants and provide more reaction centers for photocatalytic reactions. Its preparation methods include template method (hard template and soft template) and gas expansion method (such as urea thermal decomposition to introduce pores). However, the template stability of the soft template method is poor, which will lead to structural instability; the template removal requirements of the hard template method are high, the cost is high, and impurities are easily introduced; the gas expansion method is difficult to control and it is difficult to achieve a high specific surface area. In addition, regulating the morphology and dimension of the material (such as one-dimensional nanorods, two-dimensional nanosheets or three-dimensional porous networks) is also an important means. The one-dimensional structure is conducive to the directional migration of photogenerated electrons and reduces recombination; the two-dimensional nanosheets increase the exposed surface, improve light absorption and reaction efficiency; the three-dimensional porous network structure further improves the light utilization rate by enhancing multiple reflections of light. The construction of heterojunctions is achieved by combining graphene-phase carbon nitride with metal oxides (such as TiO2, ZnO, etc.) or other photocatalytic materials, which can not only broaden the light absorption range, but also promote the separation of photogenerated carriers at the interface, significantly enhancing the photocatalytic activity. In addition, doping with non-metallic or transition metal elements (such as sulfur, phosphorus, iron, cobalt, etc.) can optimize the electronic structure of graphene-phase carbon nitride, improve its photogenerated charge separation efficiency, and broaden its visible light response range, thereby further improving the photocatalytic performance.
[0004] 202210387296 discloses a method for preparing a one-dimensional nanorod-shaped carbon nitride photocatalyst and its application in the photocatalytic oxidation of monosaccharides to synthesize lactic acid. It is freeze-dried by mixing a nitrogen-containing compound precursor with a nanocellulose aqueous dispersion, calcining it under an inert atmosphere, and then hydrothermally treating it with hydrogen peroxide, thereby introducing oxygen atoms and nitrogen vacancies into the catalyst structure to achieve improved performance of photocatalytic oxidation. Although it shapes the one-dimensional nanorod-like structure of carbon nitride materials through the nanocellulose template method, improving its specific surface area and photocatalytic performance, the quality of the nanocellulose template used and the residues during the firing process will significantly affect the purity of the material. The preparation process is complicated and requires multiple steps (including freeze drying and hydrogen peroxide etching). It has high requirements for equipment conditions, and the material focuses on the direction of photocatalytic oxidation synthesis. Therefore, it is more practical to regulate the direction of material morphology only through hydrothermal reaction without adding new substances.
[0005] Further exploration of the actual application of graphite carbon nitride in the photocatalytic degradation of pollutants in water is of great significance to fully explore and improve the morphological structure of graphite carbon nitride, simplify the preparation steps, and show greater application potential of graphite carbon nitride in the field of photocatalysis. Summary of the invention
[0006] Purpose of the invention: In view of the problems existing in the prior art, the first purpose of the present invention is to provide a porous rod-shaped carbon nitride material, the second purpose of the present invention is to provide a method for preparing the porous rod-shaped carbon nitride material, and the third purpose of the present invention is to provide the application of the porous rod-shaped carbon nitride material in catalytic degradation of new pollutants of typical iodinated contrast agents under visible light conditions. By constructing a rod-shaped porous carbon nitride photocatalytic material, the photocatalytic activity of the material is significantly improved. The material has a higher specific surface area and uniform pore distribution in structure, can achieve efficient photocatalytic degradation, and shows excellent practical application potential.
[0007] Technical solution: The method for preparing a porous rod-shaped carbon nitride composite material according to the present invention comprises the following steps:
[0008] (1) dissolving melamine and urea in deionized water, performing a high temperature hydrothermal reaction, and cooling to room temperature to obtain a mixed solution;
[0009] (2) adding a phosphoric acid solution dropwise to the mixed solution obtained in step (1), washing by centrifugation, and drying to obtain a solid sample;
[0010] (3) The solid sample obtained in step (2) is calcined at high temperature in an inert gas atmosphere, cooled to room temperature, and ground to obtain a porous rod-shaped carbon nitride composite material.
[0011] Furthermore, in step (1), the molar ratio of melamine to urea is 1:2 to 1:4, preferably 1:2.8.
[0012] Furthermore, in step (1), the total molar concentration of the mixed solution is 0.227 to 0.566 mol / L, preferably 0.430 mol / L.
[0013] Furthermore, in step (1), the heating rate of the high-temperature hydrothermal reaction is 5-10°C / min, the temperature of the high-temperature hydrothermal reaction is 150-200°C, and the time of the high-temperature hydrothermal reaction is 8-12h. Preferably, the reaction is carried out at 180°C for 10h.
[0014] Furthermore, in step (2), the concentration of the phosphoric acid solution is 75-95%, and the volume ratio of the phosphoric acid solution to the mixed solution is 1:10-1:35.
[0015] Furthermore, in step (2), the centrifugal washing is performed by centrifugation washing with ethanol and deionized water for more than three times respectively.
[0016] Furthermore, in step (3), the inert gas is nitrogen or argon.
[0017] Furthermore, in step (3), the flow rate of the inert gas is 5 to 15 mL / min, preferably 10 mL / min.
[0018] Furthermore, in step (3), the heating rate of high temperature calcination is 2-5°C / min, the temperature of high temperature calcination is 400-600°C, and the time of high temperature calcination is 2-5h. Preferably, the temperature is increased to 500°C at 2.5°C / min and kept at this temperature for 4h.
[0019] The porous rod-shaped carbon nitride composite material is obtained by the preparation method of the present invention.
[0020] The porous rod-shaped carbon nitride composite material of the present invention is used in catalytic degradation of iodinated contrast agent pollutants under visible light conditions.
[0021] Furthermore, the iodinated contrast agent contaminant is one or more of iopamidol, iohexol, iopromide, iomeprol and sodium diatrizoate.
[0022] A method for catalytically degrading typical iodinated contrast agent pollutants by utilizing the porous rod-shaped carbon nitride composite material of the present invention comprises the following steps:
[0023] The porous rod-shaped carbon nitride composite material of the present invention is mixed with a solution containing iodinated contrast agent pollutants; reacted under visible light, and filtered.
[0024] Furthermore, the mass ratio of the porous rod-shaped carbon nitride composite material to the iodinated contrast agent pollutant in the solution is 1:5 to 1:25, preferably 1:10.
[0025] The porous rod-shaped carbon nitride composite material used in the present invention has a porous rod-shaped morphology, a wide light absorption range, a high light energy utilization rate, and promotes the effective separation of photogenerated electrons and holes; and at the same time exhibits excellent iopamidol degradation efficiency.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0027] The porous rod-shaped carbon nitride composite material of the present invention significantly improves the photocatalytic activity of the material. It has a higher specific surface area and uniform pore distribution in structure, and achieves efficient photocatalytic degradation while avoiding secondary pollution of by-products, showing excellent practical application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the porous rod-shaped carbon nitride composite material prepared in Example 1;
[0029] Figure 2 UV-vis-DRS images of the porous rod-shaped carbon nitride composite material prepared in Example 1 and ordinary carbon nitride;
[0030] Figure 3 FT-IR images of the porous rod-shaped carbon nitride composite material prepared in Example 1 and ordinary carbon nitride;
[0031] Figure 4 Roman spectra of the porous rod-shaped carbon nitride composite material prepared in Example 1 and ordinary carbon nitride;
[0032] Figure 5 This is a diagram showing the removal effect of the porous rod-shaped carbon nitride composite material prepared in Example 1 and ordinary carbon nitride on iopamidol;
[0033] Figure 6 The removal effect of iopamidol on porous rod-shaped carbon nitride prepared with different phosphoric acid addition amounts obtained in Example 2;
[0034] Figure 7 This is a diagram showing the removal effect of iopamidol by cyclic use of the porous rod-shaped carbon nitride composite material prepared in Example 1;
[0035] Figure 8 A diagram showing the removal effect of iopamidol on the porous rod-shaped carbon nitride composite material prepared in Example 1 at different dosages. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0037] In the following experiments, UCN represents ordinary carbon nitride, and TCN-Urea represents porous rod-shaped carbon nitride composite materials.
[0038] Example 1
[0039] 1) Melamine and urea in a molar ratio of 1:2.8 were dissolved in deionized water and stirred to obtain a mixed solution, and the concentration of the mixed solution was maintained at 0.430 mol / L, and the volume of the mixed solution was 70 mL. The mixed solution was placed in a Teflon-lined autoclave for hydrothermal reaction at 180° C. for 10 h, and then cooled to room temperature;
[0040] 2) adding 5 mL of a 95% phosphoric acid solution to the reaction solution obtained in step 1) and washing the product by centrifugation with ethanol and deionized water for three times after the floccules are completely precipitated, and drying to obtain a solid;
[0041] 3) placing the solid obtained in step 2) into a 50 mL ceramic crucible, heating the mixture to 500 ° C. at a heating rate of 2.5 ° C. / min in a muffle furnace under a nitrogen atmosphere with a nitrogen flow rate of 10 mL / min, and keeping the temperature for 4 h. After cooling to room temperature, grinding the mixture to obtain a porous rod-shaped carbon nitride composite material TCN-Urea-PA5;
[0042] In addition, urea was heated to 500°C at a heating rate of 2.5°C / min in a muffle furnace under a nitrogen atmosphere, kept warm for 4 h, and then ground to obtain common carbon nitride (UCN) after cooling to room temperature.
[0043] The porous rod-shaped carbon nitride composite material TCN-Urea-PA5 prepared in the above embodiment was characterized by scanning electron microscopy. Figure 1 shown. Figure 1 The SEM images of the porous rod-shaped carbon nitride composite material prepared in Example 1, wherein a is the SEM image at 100 μm, and b is the SEM image at 20 μm. Figure 1 It can be seen that the catalyst after hydrothermal reaction and high-temperature calcination presents a one-dimensional rod-like structure, and this morphology provides favorable conditions for improving the photocatalytic performance. The one-dimensional structure can effectively promote the directional migration of photogenerated electrons and holes, reduce the probability of recombination, and thus improve the photocatalytic efficiency. It can be observed from the high-magnification image b that there are a large number of pores on the surface and inside of the rod-like material. This porous structure can significantly increase the specific surface area, provide more active sites for the adsorption of pollutant molecules, and enhance the mass transfer performance, which is conducive to the photocatalytic reaction. The rod-like particles are distributed in a flaky manner, and the particles are evenly distributed, and no obvious agglomeration phenomenon is observed. A more uniform distribution is conducive to improving the dispersibility and stability of the material in practical applications. The SEM image shows that the surface of the rod-like material is not smooth, but has a certain degree of roughness and irregularity, which can provide more active sites and further optimize the performance of the photocatalytic reaction.
[0044] Example 1 prepared ordinary carbon nitride UCN and porous rod-shaped carbon nitride composite material TCN-Urea-PA5 (referred to as TCN-Urea) ) UV-vis-DRS characterization was performed, and the results were as follows Figure 2 shown. Figure 2 UV-vis-DRS diagrams of the porous rod-shaped carbon nitride composite material prepared in Example 1 and ordinary carbon nitride, wherein a is the comparison of the UV-visible absorption spectra of UCN and TCN-Urea, and figure b is the calculated optical band gap diagram of UCN and TCN-Urea. Figure 2 The optical properties of porous rod-shaped TCN-Urea and conventionally configured UCN were compared. Figure a shows that the ultraviolet light absorption intensity of TCN-Urea is significantly higher than that of UCN, and the absorption range is wider, especially in the ultraviolet region below 300nm. Figure b reveals that the band gap (Eg) of TCN-Urea drops from 2.99eV of UCN to 2.89eV, indicating that structural defects or doping have been introduced, resulting in a narrower band gap, which is beneficial to the absorption of visible light and electron transitions, and optimizes the migration performance of photogenerated carriers.
[0045] The conventional carbon nitride UCN and the porous rod-shaped carbon nitride composite material TCN-Urea-PA5 (referred to as TCN-Urea) prepared in Example 1 were characterized by FT-IR. Figure 3 shown. Figure 3 Figure 1 is the Fourier transform infrared spectra (FT-IR) of UCN and TCN-Urea materials, where a is the comparison diagram of infrared absorption spectra (FT-IR) of UCN and TCN-Urea, and b is the comparison diagram of infrared transmission spectra (FT-IR) of UCN and TCN-Urea. Figure 3 The differences in structure and functional groups were compared. In the 4000-3000cm-1 region, the peak intensity of TCN-Urea is significantly higher than that of UCN, which is attributed to the stretching vibration of NH and OH bonds, indicating that more nitrogen- and oxygen-containing groups were introduced on the surface of the material during the firing process. In the 1650-1000cm-1 region, TCN-Urea showed stronger vibration peaks of C=N, CN and C=O bonds, indicating that different preparation methods and calcination conditions led to the formation of richer functional groups and more regular structures in TCN-Urea materials. In addition, the change in transmittance shows that compared with UCN, the morphology of the structure of TCN-Urea has changed, and the ability to adsorb and transmit light is also different. Due to the new preparation method and the morphological differences formed during the firing process, the TCN-Urea material exhibits stronger functional group characteristics, improving the photocatalytic activity and adsorption performance of the material.
[0046] The Roman characterization was performed on the common carbon nitride UCN and the porous rod-shaped carbon nitride composite material TCN-Urea-PA5 (referred to as TCN-Urea) prepared in Example 1. The results are as follows: Figure 4 As shown. Figure 4 The Raman spectrum of the catalyst analyzes the structure and vibration mode of the material. The Raman signal intensity of TCN-Urea is significantly enhanced in the 1500-1700cm-1 region, indicating that more structural defects such as C=N bonds and lattice defects have been introduced, thereby increasing the Raman activity of the material. The Raman peak of UCN is weaker, indicating that its structure is more ordered and has fewer defects. Overall, the structure of the material is regulated during the calcination process, defect sites and active centers are introduced, and the photocatalytic performance is improved.
[0047] Example 2
[0048] The iopamidol (IPM) degradation performance test was carried out on the common carbon nitride UCN and the porous rod-shaped carbon nitride composite material TCN-Urea-PA5 (denoted as TCN-Urea) prepared in Example 1. 100 mL of 10 mg / L IPM solution was prepared in a conical flask, and 0.010 g of the UCN and TCN-Urea photocatalytic materials prepared in the above Example 1 were added to the conical flask respectively. The temperature-controlled magnetic stirring device was turned on for magnetic stirring for 30 minutes under dark conditions to allow the reaction system to reach adsorption equilibrium. After the dark reaction was completed, the light source (xenon lamp, λ>420 nm) was turned on, and the photocatalytic reaction was started. 2 mL of the sample was drawn with a syringe at fixed time intervals (reaction time of 5 min, 15 min, 30 min and 45 min, respectively), and filtered with a 0.22 μm filter membrane. The IPM concentration at different sampling times was determined by high performance liquid chromatography. The results are as follows Figure 5 As shown. Figure 5 It can be seen that the degradation effects of solar and ordinary UCN catalysts on the pollutant IPM in 45 minutes are 45% and 65% respectively, while the removal rate of the pollutant IPM by TCN-Urea catalyst in 45 minutes reaches more than 90%.
[0049] Example 3
[0050] The preparation process is the same as in Example 1, except that the amount of phosphoric acid solution added is 0, 1, 3, 4, 5, and 7 mL, respectively, and the obtained materials are labeled as TCN-Urea-PA. 、 The degradation performance of the composite materials and common carbon nitride UCN prepared in this example with different phosphoric acid addition amounts was tested, and the test process was the same as in Example 2. The results are shown in Figure 6As shown, the porous rod-shaped carbon nitride composite prepared by the method of the present invention has better effects in photocatalytic degradation than UCN. Especially under the condition of adding 1 to 5 mL of phosphoric acid, the catalytic performance is better than TCN-Urea-PA0, and TCN-Urea-PA5 has the best effect. It shows that the appropriate addition of phosphoric acid can effectively promote the complete precipitation of flocs in step 2) and maintain a good floc morphology, thereby optimizing the specific surface area and active sites of the catalyst. This optimized morphology enhances the adsorption and photocatalytic degradation performance of pollutants. The catalytic effect of TCN-Urea-PA7 decreased significantly, which may be due to the excessive addition of phosphoric acid, which caused the pH of the reaction solution to be too low, the floc structure formed during the reaction was not stable enough, some pores were blocked or collapsed, and the dispersibility was reduced, thereby reducing the specific surface area and active sites, and finally reducing the catalytic performance.
[0051] Example 4
[0052] The TCN-Urea-PA5 prepared in Example 1 was subjected to three cycles of IPM degradation cycle performance tests. The test process was the same as in Example 2. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that within 45 min, the removal rate of IPM by TCN-Urea-PA5 reached 96% in the first cycle and remained at 89% and 87% in the second and third cycles, respectively, showing high degradation efficiency and excellent cycle stability.
[0053] Example 5
[0054] The photocatalytic degradation performance of IPM was tested by adding different dosages of TCN-Urea-PA5 prepared in Example 1. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the amount of catalyst TCN-Urea-PA5 is closely related to the degradation efficiency of pollutants. When the catalyst dosage is low (such as 25mg / L or 50mg / L), the degradation efficiency is low; when the catalyst dosage increases to 100mg / L to 150mg / L, the degradation efficiency is significantly improved, and the pollutant removal effect is the best. The mass ratio of the catalyst to the pollutant in the solution corresponding to the optimal dosage range is about 1:10. At the same time, when the catalyst dosage is further increased to 200-300mg / L, the degradation efficiency tends to be stable or even slightly decreased, which may be due to the excessive accumulation of the catalyst, resulting in a reduction in active sites or a light shielding effect. Comprehensive analysis shows that the mass ratio of the amount of the catalyst porous rod-shaped carbon nitride to the pollutant is 1:(5-25) with better catalytic degradation effect, and the most preferred dosage ratio is: 1:10.
[0055] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, the present invention can be improved and modified without departing from the principles of the invention. These improvements and modifications are also within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a porous rod-shaped carbon nitride composite material, characterized in that: The steps include: (1) dissolving melamine and urea in deionized water, performing a high temperature hydrothermal reaction, and cooling to room temperature to obtain a mixed solution; (2) adding a phosphoric acid solution dropwise to the mixed solution obtained in step (1), washing by centrifugation, and drying to obtain a solid sample; (3) The solid sample obtained in step (2) is calcined at high temperature in an inert gas atmosphere, cooled to room temperature, and ground to obtain a porous rod-shaped carbon nitride composite material.
2. The method for preparing the porous rod-shaped carbon nitride material according to claim 1, characterized in that: In step (1), the molar ratio of melamine to urea is 1:2 to 1:4, and the total molar concentration of the mixed solution is 0.227 to 0.566 mol / L.
3. The method for preparing the porous rod-shaped carbon nitride material according to claim 1, characterized in that: In step (1), the heating rate of the high-temperature hydrothermal reaction is 5 to 10°C / min, the temperature of the high-temperature hydrothermal reaction is 150 to 200°C, and the time of the high-temperature hydrothermal reaction is 8 to 12 hours.
4. The method for preparing the porous rod-shaped carbon nitride material according to claim 1, characterized in that: In step (2), the concentration of the phosphoric acid solution is 75-95%, the volume ratio of the phosphoric acid solution to the mixed solution is 1:10-1:35, and the centrifugal washing is performed by centrifugation with ethanol and deionized water for more than three times.
5. The method for preparing the porous rod-shaped carbon nitride composite material according to claim 1, characterized in that: In step (3), the inert gas is nitrogen or argon, and the flow rate of the inert gas is 5 to 15 mL / min.
6. The method for preparing the porous rod-shaped carbon nitride composite material according to claim 1, characterized in that: In step (3), the heating rate of high-temperature calcination is 2 to 5°C / min, the temperature of high-temperature calcination is 400 to 600°C, and the time of high-temperature calcination is 2 to 5 hours.
7. The porous rod-shaped carbon nitride composite material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the porous rod-shaped carbon nitride composite material according to claim 7 in catalytic degradation of iodinated contrast agent pollutants under visible light conditions.
9. The use according to claim 8, characterized in that: The iodinated contrast agent contaminants are one or more of iopamidol, iohexol, iopromide, iomeprol and sodium diatrizoate.
10. A method for catalytically degrading typical iodinated contrast agent pollutants using the porous rod-shaped carbon nitride composite material according to claim 7, characterized in that: The steps include: The porous rod-shaped carbon nitride composite material according to claim 7 is mixed with a solution containing iodinated contrast agent pollutants, reacted under visible light, and filtered.
Citation Information
Cited By
Rod-like carbon nitride-based zinc cadmium sulfide composite photocatalytic material as well as preparation method and application thereof
CN121266612A